Analysis of Experience and Knowledge Competencies of Teacher Scientific Performance in Batu City Middle Schools - Eko Susetyarini; Ainur Rofieq; Roimil Latifa; Supiana Dian Nurtjahyani; Endrik Nurrohman (Jurnal Penelitian Pendidikan IPA, 2023)
One of the efforts that teachers can undertake to strengthen their professionalism as educators is writing scientific papers and teaching materials. This study aims to analyze knowledge and scientific performance competency in designing and carrying out Classroom Action Research of the teachers in SMP Muhammadiyah 8, Batu City. This study was descriptive study. This study was conducted from July to November 2022. The population and samples of this study were the teachers of Batu City Middle Schools. The procedures of this study encompassed preparation and research implementation. The number of respondents was 30 teachers. Interviews and questionnaires were used as the data collection procedures of this study. The knowledge aspects studied from the teacher's scientific performance competence were formulating appropriate research problems, developing a literature study framework, compiling a conceptual framework, and analyzing research results data. The data analysis technique used in this study was a descriptive-analytic by describing the findings of the study. The results of this study indicate that: that experience in the form of undergraduate education background is higher (66.76%) than master (33.38%); being a teacher for less than 15 years or less (33.00%), over 15 years is 67.00%; experience doing research is 83.00% and performance competency knowledge in the field of scientific work of Batu City Middle School teachers is in the sufficient and good categories. This study recommends that correlation analysis (correlation regression) is required between the professionalism aspect, particularly in terms of teacher scientific field performance, and assistance is needed to improve teachers’ competencies thru collaborative academic activities between lecturers and teachers in schools; one of the activities is thru a Lecturer Partnership Program.